Strengthening Civil Servant Competency to Improve Public Service Performance: A Regulatory Evaluation Perspective - Rohani Rohani; Raden Biroum; Soesilo Wibowo (Jurnal Kebijakan Publik, 2025)
This study addresses the issue of suboptimal public service delivery, which is often attributed to gaps in the competencies of civil servants (ASN), especially in the areas of technical and managerial capacity. The main objective of the research is to evaluate the extent to which civil servant competencies influence public service performance, guided by Government Regulation No. 30 of 2019 on Civil Servant Performance Assessment. The study also aims to identify the supporting and inhibiting factors that affect competency fulfillment in delivering effective services. Using a qualitative descriptive approach, the research was conducted at the Social Affairs Office of West Kotawaringin Regency. Subjects involved in this study included structural officials, functional staff, and administrative personnel. Data were collected through direct observation, in-depth interviews, and documentation, while the analysis employed qualitative content analysis techniques. The findings reveal that civil servants demonstrate adequate socio-cultural competencies, such as empathy and adaptability in community interactions. However, deficiencies were identified in technical skills, especially among new employees unfamiliar with digital systems, and in managerial practices, including poor coordination and unclear delegation. Public service performance—measured through effectiveness, efficiency, and economy—was hindered by outdated infrastructure, excessive reliance on manual processes, and budget inefficiencies. Supporting factors include clear regulatory frameworks, committed leadership, and basic facilities. Meanwhile, constraints include limited training opportunities, inadequate staffing, and poor digital data management. The study concludes that enhancing civil servant competencies through targeted training, integrated digital systems, and strategic resource planning is crucial to improving public service performance. These findings have practical implications for strengthening human resource development policies in local government administration.